Hydroxychloroquine's Efficacy as an Antiplatelet Agent Study in Healthy Volunteers: A Proof of Concept Study. (March 2015) - Achuthan, S.; Ahluwalia, J.; Shafiq, N.; Bhalla, A.; Pareek, A.; Chandurkar, N.; Malhotra, Samir
Background: With the inflammatory model of atherosclerosis taking center stage, anti-inflammatory drugs hold a promising place in the therapy of cardiovascular disease (CVD). Recent studies showed that hydroxychloroquine (HCQ) was protective against thrombovascular events in lupus erythematosus and traditional cardiovascular risk factors in patients with rheumatoid arthritis. Some preliminary experimental data have shown that it may prevent platelet activation too. Objective: To evaluate the antiplatelet activity of HCQ when given alone and in combination with aspirin (ASA) and compare it with ASA alone and ASA plus clopidogrel (CLOP) in healthy human volunteers. Methods: In part 1 of the study, 8 volunteers were given HCQ for 7 days. In part 2, 12 volunteers were randomly assigned in a 1:1:1 ratio to the 3 groups in which 2 of the 3 treatments, ASA, ASA plus CLOP, and ASA plus HCQ, were given in the 2 treatment periods separated by a 14-day washout period using the incomplete block design. Inhibition of platelet aggregation (IPA) was measured by light transmission aggregometry. Results: When arachidonic acid (AA) was used as agonist, HCQ given alone showed a significant reduction in platelet aggregation (11.0% ± 4.2%, P = .03). The IPA was significantly increased when ASA plus HCQ was compared with ASA alone (31.2% ± 8.1%, P = .002). This synergistic effect was not seen with adenosine diphosphate and collagen as agonists. Levels of serum 11-dehydrothromboxane B2, a stable marker of thromboxane A2 production, were not significantly different between the groups. There was also a significant decrease in fibrinogen and erythrocyte sedimentation rate values when HCQ was used alone or in combination with ASA. Conclusion: This study suggests that HCQ has antiplatelet properties possibly through the AA pathway (downstream to thromboxane A2 production). With possible additional beneficial effects over the traditional CVD risk factors, larger studies in the future might explore HCQ's potential as an antiplatelet agent.